Exchange-field-controllable 0-π transition in asymmetric Josephson spin-valve heterostructure - Choopan, Wachiraporn (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 2 (2021): April-June 2021DO - 10.14456/nujst.2021.20, 2020)
The Josephson Effect in an asymmetric SIFM 1 IFM 2 IS Josephson Junction (JJ) in which the two SIF bilayers have different ferromagnetic layers (FM 1 and FM 2 ) is studied.  The linearized Usadel equations, which are valid for low transparency interfaces between S and FM layers, are used to obtain the expressions for the critical current in this junction.  The relative magnitudes and directions of the exchange fields in (FM 1 and FM 2 ) are treated as adjustable parameters.  The Josephson currents in this junction are simulated by numerically evaluating the expressions for various values of the adjustable parameters.  We consider the cases of the exchange fields in the two ferromagnetic layers being parallel and being antiparallel.    We show that increasing the exchange field in the first layer of a parallel aligned junction while maintaining the value of the exchange field in the second layer will induce a “0-π” transition, i.e., a reversal of the direction of the current, but that increasing the exchange field in an antiparallel alignment will not.  When the exchange field in the second layer in a parallel aligned SIFM 1 IFM 2 IS junction is large, it is seen that a small change of the exchange field in the first layer can induce the switch of “0-state” JJ to a “π-state” JJ in the entire temperature range of operation (0 < T < T c ) of the junction. PACS classification codes: 74.80.Dm; 74.50.+r; 75.30.Et; 74.60.Jg Keywords: Josephson junction, Ferromagnet, Critical current, Spintronic, Electronic switching